2005
DOI: 10.1007/s00213-005-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

β2-Subunit-containing nicotinic acetylcholine receptors are involved in nicotine-induced increases in conditioned reinforcement but not progressive ratio responding for food in C57BL/6 mice

Abstract: These data show that nicotine exposure enhances conditioned reinforcement in mice and indicate that beta2*nAChRs are necessary for nicotine-dependent enhancement of incentive aspects of motivation but not motivation for primary reinforcement measured by progressive ratio responding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 63 publications
6
56
1
Order By: Relevance
“…DHβE, an α4β2-selective antagonist, effectively decreased the nicotine-enhanced lever responses. This finding is in line with previous studies showing that knockout of β2-subunit of the nAChRs cancelled the ability of nicotine to enhance responding for a food-conditioned reinforcement (Brunzell et al 2006) and that DHβE reversed nicotine-induced potentiation of the electrical stimulation reward (Harrison et al 2002;Kenny and Markou 2006). However, the α7-selective antagonist MLA did not change magnitude of nicotine-enhanced responding.…”
Section: Discussionsupporting
confidence: 92%
“…DHβE, an α4β2-selective antagonist, effectively decreased the nicotine-enhanced lever responses. This finding is in line with previous studies showing that knockout of β2-subunit of the nAChRs cancelled the ability of nicotine to enhance responding for a food-conditioned reinforcement (Brunzell et al 2006) and that DHβE reversed nicotine-induced potentiation of the electrical stimulation reward (Harrison et al 2002;Kenny and Markou 2006). However, the α7-selective antagonist MLA did not change magnitude of nicotine-enhanced responding.…”
Section: Discussionsupporting
confidence: 92%
“…The possibility that our manipulations also affect instrumental learning processes can, however, not be completely excluded. In support of our conclusions, the increase in instrumental performance observed after previous oral cocaine exposure (Miles et al, 2004) has been argued to involve motivational alterations consistent with the ability of chronic nicotine treatment to increase progressive ratio responding in mice (Brunzell et al, 2006). Furthermore, dopamine transporter knock-out mice, in which extracellular dopamine levels are increased, display both enhanced ⌬FosB immunoreactivity and food-reinforced motivation, but not altered learning (Cagniard et al, 2006).…”
Section: Discussionsupporting
confidence: 85%
“…Whereas mRNA levels for galanin receptors are low in the NAc, galanin receptor binding is quite prominent (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), indicating that localization of galanin receptors on DA terminals might regulate DA release. Galanin is also known to be a potent inhibitory modulator of basal acetylcholine (ACh) release in the striatum (Antoniou et al, 1997) and it has been demonstrated that M1-muscarinic receptors and high-affinity nicotinic receptors regulate the secondary rewarding effects of cues paired with a primary reinforcer such as morphine (Brunzell et al, 2006;Carrigan and Dykstra, 2007). Lack of galanin may therefore increase availability of ACh, thus increasing the sensitivity of GKO mice to opiates.…”
Section: Discussionmentioning
confidence: 99%